Key degradation mechanisms of perovskite solar cells and strategies for enhanced stability : issues and prospects - Md. Helal, Miah; Md. Bulu, Rahman; Mohammad, Nur-E-Alam; Mohammad Aminul, Islam; M., Shahinuzzaman; Md Rezaur, Rahman; Md. Habib, Ullah; Mayeen Uddin, Khandaker (The Royal Society of Chemistry (RSC), 2025)
Perovskite materials have garnered significant attention within a very short period of time by achieving competitive efficiency. In addition, this material demonstrated intriguing optoelectronic properties and versatile applications. Although they have confirmed amazing efficiency in solar cells at the laboratory scale, mass commercial manufacturing of perovskite solar cells (PSCs) is still a problem due to their poor longevity. Researchers have identified several intrinsic and extrinsic factors contributing to the instability of perovskite compounds and PSCs, and various approaches are being used to increase material quality and stability in order to extend the lifespan of PSCs. Despite these challenges, the potential of perovskite materials in revolutionizing solar energy remains a central point of scientific investigation and development. In this review, a comprehensive analysis is provided to discern the intrinsic and extrinsic factors contributing to the degradation of PSCs which certainly helps us to understand the underlying degradation mechanisms. In addition, we discussed some novel approaches that have already been adopted to augment the stability of the devices.